Brief report: Correlates of inpatient psychiatric admission in children and adolescents with eating disorders - Hamilton, M.; Watson, H.; Egan, Sarah; Hoiles, K.; Harper, E.; McCormack, J.; Forbes, D. (Academic Press, 2015)
Objective: To examine the prevalence and importance of psychological, behavioural, and situational correlates of impending psychiatric inpatient admissions in children and adolescents with eating disorders. Method: The sample consisted of 285 patients (8-17 years, M=14.4, SD=1.49) with DSM-5 eating disorders assessed between 2006 and 2013 from the Helping to Outline Pediatric Eating Disorders (HOPE) Project. The sample was split into two groups, those with (n=38) and without (n=247) impending psychiatric admission; Discriminant function analysis was used to examine correlates. Results: The prevalence of impending psychiatric admission was 13.3%. Suicidal ideation provided the greatest discriminating power, followed by eating pathology, depressive symptoms, anxiety, multiple methods of weight control, binge eating, and family functioning. Conclusions: Earlier recognition of comorbid symptoms in eating disorders in the community may reduce the number of young people with eating disorders who present needing critical psychiatric care.